Mastitis and death of a Corriedale ewe associated with Mycoplasma spp. infection in Buenos Aires province - Canton, German Jose (2021)
Mycoplasma spp. infections are associated with different clinical syndromes in ruminants: mastitis, pneumonia, arthritis, otitis, among others. Nevertheless, case reports of clinical diseases associated with Mycoplasma-infections are scarce in small ruminants of Argentina. Mycoplasma agalactiae and Mycoplasma capricolum are the causal agents of contagious agalactia, an exotic disease in the region. Therefore, strict surveillance of these pathogens is needed. Severe mastitis of a 7-years-old Corriedale ewe in a flock from Buenos Aires province is reported. The affected ewe had delivered twin lambs 15 days before the clinical disease was detected and died. During post mortem examination, supramammary lymphadenomegaly was evident. Mammary gland was enlarged and firm, with cyanotic skin and superficial edema; multiple caseous whitish foci were observed in the mammary parenchyma. Similar caseous foci were observed in the caudal-ventral lobes of the right lung. In the histopathological analysis, chronic multifocal necrotizing severe mastitis and fibrinous bronchopneumonia with multifocal necrosis and fibrinous pleurisy were observed. Mycoplasma spp. was isolated from the mammary gland. Mycoplasma spp. nested-PCR resulted positive in mammary gland and lung. Sequencing analysis confirmed the presence of Mycoplasma arginini and Mycoplasma bovis in mammary gland and lung, respectively. The pathological findings were similar to the described in cases of contagious agalactia, therefore, Mycoplasma speciation was decided in order to discard the presence of this exotic disease.